(untitled) (Texas Journal of Medical Science, 2022)
The aim of this work was to elucidate the structural bases of the reaction of blood system cells in acute and chronic herbicide poisoning and to find spores for their correction with metal-containing biocomplexes. Based on the goal, the following tasks were set: - to study the morphofunctional state of various (copper-containing cobalt) biocomplexes on the morphofunctional state of the cells of the blood system in acute and chronic herbicide poisoning